1999
DOI: 10.1021/jp990867n
|View full text |Cite
|
Sign up to set email alerts
|

Conformations and Barriers of Haloethyl Radicals (CH2XCH2, X = F, Cl, Br, I):  Ab Initio Studies

Abstract: Radicals such as CH 2 XCH 2• , where X is a halogen, play an important role in the stereochemical control observed in many chemical reactions. To elucidate the origin of the stereoselectivity, we calculated the structures and potential energy surfaces of the haloethyl radicals (CH 2 XCH 2 • , X ) F, Cl, Br, I) using ab initio quantum mechanics [HF, local MP2, DFT (both B3PW91 and B3LYP)]. We find that the CH 2 BrCH 2• and CH 2 ICH 2• radicals strongly favor the symmetrically bridged structures while the CH 2 C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
50
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 69 publications
6
50
1
Order By: Relevance
“…Our higher theoretical level estimate for the rotational barrier [QCISD(T)/aug-cc-pVDZ//QCISD/6-31G(d,p)] is 2.1 kcal/mol (see Table 2). Furthermore, data in Tables 2-5 show that our computed barrier lies between 1.8 [MP2/6-311++G(3df,3pd)] and 3.1 kcal/mol [Becke3LYP/6-31G(d,p)], lower than the ESR estimated value and in good agreement with those of Ihee et al 28 V. 1,2 Hydrogen Shift. The most stable form of the chloroethyl radical is the 1-chloroethyl radical (see Tables 2-5).…”
Section: Table 1: Most Significant Geometrical Parameters As Computedsupporting
confidence: 87%
See 2 more Smart Citations
“…Our higher theoretical level estimate for the rotational barrier [QCISD(T)/aug-cc-pVDZ//QCISD/6-31G(d,p)] is 2.1 kcal/mol (see Table 2). Furthermore, data in Tables 2-5 show that our computed barrier lies between 1.8 [MP2/6-311++G(3df,3pd)] and 3.1 kcal/mol [Becke3LYP/6-31G(d,p)], lower than the ESR estimated value and in good agreement with those of Ihee et al 28 V. 1,2 Hydrogen Shift. The most stable form of the chloroethyl radical is the 1-chloroethyl radical (see Tables 2-5).…”
Section: Table 1: Most Significant Geometrical Parameters As Computedsupporting
confidence: 87%
“…47 Engels et al 23 computed (MRD-CI) a value (without optimization of the transition structure) of 4.3 kcal/mol while the MP4/6-311G-(d,p)//MP2/6-31G(d) barrier is 2.1 kcal/mol. 48 Ihee et al 28 reported the values 1.8 (LMP2) and 3.5 (Becke3LYP) kcal/mol. Our higher theoretical level estimate for the rotational barrier [QCISD(T)/aug-cc-pVDZ//QCISD/6-31G(d,p)] is 2.1 kcal/mol (see Table 2).…”
Section: Table 1: Most Significant Geometrical Parameters As Computedmentioning
confidence: 99%
See 1 more Smart Citation
“…41,48,49 Moreover, recent computational investigations show that B3LYP calculations describe quite well the behavior of internal bond rotation of open-shell chemical species. 50,51 Thus, we examined the rotational energy profiles of the substituted methyl radicals by using B3LYP 42 and QCISD(T) 43 calculations. The values of µ and η were calculated according to three-point approximation, namely eqs 2a and 2b.…”
Section: Computational Detailsmentioning
confidence: 99%
“…EPR and X-ray crystallographic data for several coenzyme B 12 -dependent systems indicate that intermediate free radicals are bound some distance from cob(II)alamin (e.g., 6.5 in glutamate mutase [5]). It is therefore expected that the barrier to rotation about the s-bond between the methylidene Catom bearing the radical and the adjacent C-atom in the product-related radical for all coenzyme B 12 -dependent C-skeleton rearrangements will be relatively low (n.b., there is essentially free rotation in the ethyl radical [6]) and hardly perturbed by the Co-atom of cob(II)alamin.…”
mentioning
confidence: 99%